2017
DOI: 10.1016/j.bbr.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Systemic cisplatin exposure during infancy and adolescence causes impaired cognitive function in adulthood

Abstract: Cancer survivors diagnosed during infancy and adolescence may be at risk for chemotherapy-related cognitive impairments (CRCI), however the effects of pediatric chemotherapy treatment on adulthood cognitive function are not well understood. Impairments in memory, attention and executive function affect 15–50% of childhood leukemia survivors related to methotrexate exposure. Systemic cisplatin is used to treat a variety of childhood and adult cancers, yet the risk and extent of cognitive impairment due to plati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 43 publications
(47 reference statements)
0
14
0
1
Order By: Relevance
“…In addition, the influence of chemotherapy cannot be excluded in extensive GM deficits. According to one previous study, platinum-based chemotherapy exposure reduced dendritic branching and spine volume, and induced apoptosis of neurons and NSC within the hippocampal formation (24). The alteration of GM volume was observed in breast cancer because some cytotoxic agents, mainly including 5-FU, thiotepa and cyclophosphamide, can cross over the blood brain barrier, and disrupt cell division in the brain regions that are critical for memory and learning (25).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the influence of chemotherapy cannot be excluded in extensive GM deficits. According to one previous study, platinum-based chemotherapy exposure reduced dendritic branching and spine volume, and induced apoptosis of neurons and NSC within the hippocampal formation (24). The alteration of GM volume was observed in breast cancer because some cytotoxic agents, mainly including 5-FU, thiotepa and cyclophosphamide, can cross over the blood brain barrier, and disrupt cell division in the brain regions that are critical for memory and learning (25).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 60% (range 26‐90%) children receiving cisplatin develop irreversible bilateral hearing loss, which may have a deleterious effect in their speech, language, and social skills . Cisplatin exposure has also been associated with cognitive dysfunction, the so‐called “chemo‐brain”, which is beyond the scope of this review …”
Section: Clinical Aspects Of Pipnmentioning
confidence: 96%
“…the brain, and several clinical studies reported that patients of all ages treated with doxorubicin exhibited impaired ability in cognitive assessments (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…In addition, doxorubicin causes the production of invasive systemic reactive oxygen species (ROS) ( 9 ). Notably, despite its limited passage through the blood-brain barrier (BBB), doxorubicin can still cause severe neurotoxicity in the brain, and several clinical studies reported that patients of all ages treated with doxorubicin exhibited impaired ability in cognitive assessments ( 10 13 ).…”
mentioning
confidence: 99%